2019
DOI: 10.1186/s12966-019-0873-7
|View full text |Cite
|
Sign up to set email alerts
|

The neighborhood social environment and physical activity: a systematic scoping review

Abstract: BackgroundInvestigating the association of the neighborhood social environment on physical activity is complex. A systematic scoping review was performed to (1) provide an inventory of studies assessing the influence of the neighborhood social environment on physical activity since 2006; (2) describe methodologies employed; and (3) formulate recommendations for the field.MethodsTwo databases were searched using terms related to ‘physical activity,’ ‘neighborhood,’ and ‘social environment’ in January 2017. Elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 84 publications
(109 reference statements)
4
57
0
6
Order By: Relevance
“…It seems to be demonstrated that the accessibility and availability of spaces and the aspects related to the neighborhood environment influence the level of physical activity. Other studies also showed the influence of the neighborhood on physical activity levels [41].…”
Section: Discussionmentioning
confidence: 97%
“…It seems to be demonstrated that the accessibility and availability of spaces and the aspects related to the neighborhood environment influence the level of physical activity. Other studies also showed the influence of the neighborhood on physical activity levels [41].…”
Section: Discussionmentioning
confidence: 97%
“…Differences in environmental factors, physical activity levels and genetic factors may produce a variability in the blood pressure response to physical activity at the population level [ 40 ]. A recent systematic scoping review of the neighborhood social and built environment and physical activity highlighted the need for further studies in which environmental factors would be key influencers of physical activity [ 41 , 42 ]. There is some indication that the investigation of the context-specific built environment associations and improving neighborhood walkability and the quality of parks may have a positive impact on the policy change process and may increase physical activity [ 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence is limited and future studies are needed including data on social ties to examine this hypothesis. It is also possible that other unmeasured geospatial and social environmental factors are confounding this effect, such as neighborhood social capital ( Kepper et al, 2019 ). Neighborhoods are complex and dynamic environments that may be characterized as both low SES and high social capital, where the benefits of social capital may buffer the negative association between low SES and MVPA ( Loh et al, 2019 , Cradock et al, 2009 , Elgar et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%